The reliability of tax data for measuring disposable income inequality in Poland - Gorazda, Marcin; Kwarciński, Tomasz (Ruch Prawniczy, Ekonomiczny i Socjologiczny, 2025)
This paper critically examines the suitability of tax data for measuring disposable income inequality, with a focus on the Polish income tax system. It assesses the limitations of relying solely on tax data and proposes an alternative approach that combines survey data with administrative records for improved accuracy. The analysis draws on data from tax reports, national accounts, and a review of relevant literature on taxpayer behaviour. By analysing issues such as discrepancies between disposable income and total income, misreporting, and adaptive taxpayer responses to tax regulations, the study highlights the complexity and volatility of tax systems. The findings suggest that researchers need a thorough understanding of both tax law and taxpayer behaviour to avoid substantial errors in measuring income inequality accurately.